Enhanced Raman Scattering of Graphene using Arrays of Split Ring Resonators. Issue 2 (12th February 2013) - Sarau, George; Lahiri, Basudev; Banzer, Peter; Gupta, Priti; Bhattacharya, Arnab; Vollmer, Frank; Christiansen, Silke
<x xml:space="preserve">Abstract</x> Combining graphene with plasmonic nanostructures is currently being explored for high sensitivity biochemical detection based on the surface‐enhanced Raman scattering (SERS) effect. Here, a novel and tunable platform for understanding SERS based on graphene monolayers transferred on arrays of split ring resonators (SRRs) exhibiting resonances in the visible range is introduced. Raman enhancement factors per area of graphene of up to 75 are measured, demonstrating the strong plasmonic coupling between graphene and the metamaterial resonances. Apart from the incident laser light, both the photoluminescence signal emitted by the SRRs and the Raman scattered light from graphene contribute to the excitation of distinct resonances, resulting in different SERS. This new perspective allows control of SERS in the case of graphene on plasmonic metamaterials or nanostructures and potentially paves the way towards an advanced SERS substrate that could lead to the detection of single molecules attached to graphene in future biochemical sensing devices.